The Values ​​of Moral Education in the Qur'an and Their Implications for the Process of Character Formation of Children or Students (Analysis Study of Surah Luqman Verses 14-15) - Maimunah Munthe; Nurul Aulia; Umii Hanifaa; Muhammad Asraf Danil (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The problem of moral decline has plagued several young generations recently, including widespread incidents of profanity, crime, violence, hate speech and other deviant behavior. Moral or character education is seen as an alternative way out of these various problems. This study of Luqman's letter is an example for parents to return to their parents' nature when providing education, morals or character and attention to their children through the example of Luqman Al-Hakim's character. The background of this research is to look at the current moral damage of children, so this research aims to provide some solutions in the form of theories to shape children's character in accordance with the teachings of the Islamic religion. This research is a type of library research, namely research whose research topic uses library data in the form of books as a source of information. This research was carried out through reading, studying and analyzing existing literature in the form of the Al-Quran, other books and research. This research uses a qualitative approach, namely systematic research where objects are researched or researched in a natural environment without manipulation and without testing hypotheses. The results of this research are that there is several moral education in Surah Al-Luqman verses 14 and 15, including filial piety to parents, the command to always be grateful and patient, and to be aware of the place of human return and not to associate partners with Allah SWT or shirk. Then the implications that need to be emphasized in shaping children's character are birrul walidain, being grateful, being aware that humans are servants and not committing shirk.